Relation between sagittal pelvic and thoracolumbar parameters in supine position – Pelvic parameters and their predictive value for spinal Cobb angles - Arija Jacobi; Philipp Schenk; Esra Aydin; Friederike Klauke; Thomas Mendel; Bernhard W. Ullrich (Brain and Spine)
Introduction: Predicting the pre-morbid sagittal profile of the spine or segmental angles could enhance the process of planning the extent of fracture reduction. There is evidence that spinopelvic parameters may be suitable for this purpose. Research question: Is it possible to determine the inflection point and the mono- and bi-segmental endplate angles (EPA) in the thoracolumbar transition (from Th9 to L2) based on age, gender, spinopelvic parameters, and the adjacent EPA in the supine position? Material and methods: Based on Polytrauma CT scans in the supine position, the following spinopelvic parameters were measured using non-fractured spines: pelvic incidence (PI), sacral slope (SS), lumbar lordosis (LL), and the apex of the LL. Results: In this study, a total of 287 patients with a mean age of 42±16 years were included. Age-related changes were observed, where LL, thoracic kyphosis (TK), and PI increase with age. Gender-related comparisons showed that females had a more pronounced LL and reduced TK. Significant correlations between IP and spinopelvic parameters, with the apex of LL providing the best prediction, were found. However, the overall model quality remained low. Predicting mEPA and bEPA showed positive correlations. The prediction for mEPA L2/3 demonstrated the highest correlation. For bisegmental angles, the most caudal bEPA (L2) exhibited the highest correlation, albeit with some notable absolute differences in the values between measured and predicted values. Discussion and conclusion: While this study highlights the complexity of the relationship between the pelvis and thoracolumbar parameters, finding a predictive tool for thoracolumbar reduction and stabilization was not possible.